AnTScan: Android Application Testing and Scanning - Ariff Irfan Abdul Rahman,; Mohd Azahari Mohd Yusof, (Applied Information Technology And Computer Science, 2023)
Abstract: Vulnerability assessment, also known as vulnerability scanning, is a testing process used to identify security flaws and vulnerabilities in computer systems, networks, applications, and infrastructure. It is also a procedure for determining the severity level of security vulnerabilities. This paper was produced to propose a vulnerability scanning tool that currently has limitations such as taking longer to complete the analysis process, categorizing vulnerabilities, and using command line interface. The objective of this project is to develop a vulnerability scanning tool capable of identifying vulnerabilities in an Android application as well as information about the application. This tool is being created using Python language. The tool is being developed based on prototyping model. The expected outcome for this project is the development of a vulnerability scanner capable of identifying vulnerabilities in a shorten time and reducing the number of vulnerabilities in an Android application.